Basics of Stem Cells Therapy - Asmaa Monir Soliman Eltaweel (Indonesian Journal of Global Health Research, 2022)
Regeneration of a lost tissue is known to be great challenge for several years, in the recent past the research on regenerative medicine has gained great importance and scientific advancements in the field of molecular biology. Understanding the biological concepts in the tissue regeneration coupled with experiments on stem cells is likely to result in a great shift in the therapeutic medicine. Stem cells have been successfully isolated from variety of human tissues. Initial evidence from pioneering studies has documented that stem cells play vital role in treatment for various life-threatening diseases that have so far defeated modern medical care. The recent studies have been exploring the role of stem cells and their applications. This review discusses in brief the origin of stem cells, their properties, characteristics. It also focuses on current research, their potential applications and the various challenges and barriers that we must overcome before translating laboratory results to successful clinical applications.